Urgency of SQ (Spiritual Quotient) in Supporting Islamic Education Success - Bahrul Ulum; Mahsun Jayadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2017)
Spiritual Quotient (SQ), now being warmly discussed on various occasions. Various perspectives and approaches of it are being developed from science, psychology and religion. This study aims to explore what the meaning of SQ is, how successful Islamic education is, and how urgency of SQ in supporting the success of Islamic education is. This type of research includes literature study with hermeneutic approach, and the source data are books about education, psychology, aspects of intelligence. Data collection technique used is documentation technique and is analyzed by deductive and inductive methods. The findings of this study can be summarized: firstly, spiritual quotient is the human ability to solve problems that originate in empirical facts and conscience; secondly, Islamic education is said to succeed when it has been able to develop the cognitive, affective and psychomotor aspects of the students. And more importantly, the development of the three domains is a change that can bridge the individual with society and individuals with his Kholiq (creator); thirdly, SQ is very important in realizing the success of Islamic education because SQ can help to improve the ability of students in developing their spheres. Keywords: SQ meaning, Islamic education success, SQ urgency